2022
DOI: 10.3390/ijms231911239
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Seven-Day Exposure to Silver Nanoparticles on Fertility and Homeostasis of Zebrafish (Danio rerio)

Abstract: Silver nanoparticles (AgNPs) are found in open waters, but the effect of their low concentrations on an organism’s homeostasis is not fully understood. The aim of the study was to determine the short-term exposure effects of AgNPs coated by PvP (polyvinylpyrrolidone) on the homeostasis of livers and gonads in zebrafish. Sexually mature zebrafish were exposed for seven days to silver ions (0.01 mg/dm3) or AgNPs (0.01; 0.05; 0.1; 0.5; 1.0 mg/dm3). On the last day, the liver, testes, and ovaries were subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…One of the biggest concerns in case of nanoparticles is their persistence in the environment. The toxic influence of AgNPs and CuNPs is mainly observed in water environments [ 12 ]; however, some researchers point out that CuNPs are more toxic than AgNPs [ 13 ]. The exposure to NPs can cause several negative changes in the aquatic organisms, e.g., increased oxidative stress, reproductive disorders or impairing activity of the immune system [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the biggest concerns in case of nanoparticles is their persistence in the environment. The toxic influence of AgNPs and CuNPs is mainly observed in water environments [ 12 ]; however, some researchers point out that CuNPs are more toxic than AgNPs [ 13 ]. The exposure to NPs can cause several negative changes in the aquatic organisms, e.g., increased oxidative stress, reproductive disorders or impairing activity of the immune system [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The toxic influence of AgNPs and CuNPs is mainly observed in water environments [ 12 ]; however, some researchers point out that CuNPs are more toxic than AgNPs [ 13 ]. The exposure to NPs can cause several negative changes in the aquatic organisms, e.g., increased oxidative stress, reproductive disorders or impairing activity of the immune system [ 12 ]. On the other hand, there are several experiments proving that the effect of NPs on living organisms can be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Las NPs absorbidas, gracias a la reactividad ultra alta en comparación con los materiales a granel en tamaño microescala, alteran la homeostasis del cuerpo como resultado de la interacción con moléculas biológicas como el ADN, los lípidos y las proteínas; además, pueden interferir con el funcionamiento de las células, órganos y sistemas fisiológicos, lo que conduce a graves disfunciones patológicas. Szudrowicz, et al (2022) estudiaron el efecto a corto plazo de NPsAg recubiertas con polyvinylpyrrolidone (PvP) en peces cebra (Danio rerio) sexualmente maduros, lo cuales fueron expuestos durante siete días a iones de plata (0.01 mg/dm 3 ) o NPsAg (0.01; 0.05; 0.1; 0.5; 1.0 mg/dm 3 ). El último día, el hígado, los testículos y los ovarios se sometieron a un análisis histológico, el cual mostró que las NPsAg y los iones de plata provocan un aumento del área de los hepatocitos.…”
Section: Aplicaciones De La Nano-tecnología En La Reproduc-ción Animalunclassified
“…Studies investigating nano-toxicity in various species of female fish have indicated that silver (Ag) nanoparticles can inhibit the release of steroid hormones from ovarian cells of Oryzias melastigma (Degger, Anna et al 2015). Ag nanoparticles were also found to affect meiosis and cause oxidative stress in Zebrafish gonads (Szudrowicz, Kamaszewski et al 2022). In a study conducted on zebrafish, Dayal, Thakur et al (2016) stated that gold nanoparticles cause damage to the ovarian structure.…”
Section: Effects Of Nano Pollutants On Fish Reproductive Systemmentioning
confidence: 99%